Animation Use and Fifth-Grade Students’ English Skills Performance - Abdullah Issa Subh (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: English language instruction has evolved substantially from the grammar-focused Latin-based methods of the 1700s to contemporary multimedia approaches. Specific Background: Integrating animation into English as a Foreign Language (EFL) classrooms is a promising strategy, yet its direct impact on students’ four language skills remains underexplored. Knowledge Gap: Despite growing interest in multimedia-enhanced learning, empirical evidence on animation’s effectiveness in improving all four English skills at the preparatory level is limited. Aim: This study investigates the influence of animation on fifth-preparatory students’ performance across listening, speaking, reading, and writing in Al Noor preparatory private school. Results: Using an experimental design with 61 students from comparable socio-economic backgrounds, findings reveal no significant disparities between the experimental (animation-based) and control (traditional) groups in the four skills, although t-test results indicate a substantial positive impact of animation on engagement and overall performance. Novelty: This research provides one of the first systematic evaluations of animation’s role in a holistic EFL skill set within a preparatory school context. Implications: The study highlights animation as a valuable tool to enhance motivation, reduce teacher workload, and encourage broader integration of multimedia in English instruction, paving the way for future research on technology-driven language learning. Highlights: Animation enhances motivation and engagement in EFL classrooms. No significant difference found between animation and traditional methods. Supports future integration of multimedia in English instruction. Keywords: Animation, English Language Skills, EFL, Multimedia Learning, Student Performance